miR‐205 mediates adaptive resistance to MET inhibition via ERRFI1 targeting and raised EGFR signaling - Cristina Migliore; Elena Morando; Elena Ghiso; Sergio Anastasi; Vera P Leoni; Maria Apicella; Davide Cora'; Anna Sapino; Filippo Pietrantonio; Filippo De Braud; Amedeo Columbano; Oreste Segatto; et al. (EMBO Molecular Medicine, 2018)
Abstract The onset of secondary resistance represents a major limitation to long‐term efficacy of target therapies in cancer patients. Thus, the identification of mechanisms mediating secondary resistance is the key to the rational design of therapeutic strategies for resistant patients. MiRNA profiling combined with RNA‐Seq in MET‐addicted cancer cell lines led us to identify the miR‐205/ERRFI1 (ERBB receptor feedback inhibitor‐1) axis as a novel mediator of resistance to MET tyrosine kinase inhibitors (TKIs). In cells resistant to MET‐TKIs, epigenetically induced miR‐205 expression determined the downregulation of ERRFI1 which, in turn, caused EGFR activation, sustaining resistance to MET‐TKIs. Anti‐miR‐205 transduction reverted crizotinib resistance in vivo, while miR‐205 over‐expression rendered wt cells refractory to TKI treatment. Importantly, in the absence of EGFR genetic alterations, miR‐205/ERRFI1‐driven EGFR activation rendered MET‐TKI‐resistant cells sensitive to combined MET/EGFR inhibition. As a proof of concept of the clinical relevance of this new mechanism of adaptive resistance, we report that a patient with a MET‐amplified lung adenocarcinoma displayed deregulation of the miR‐205/ERRFI1 axis in concomitance with onset of clinical resistance to anti‐MET therapy.